Perancangan Aplikasi Sistem Penggajian Karyawan Pada PT Immortal Cosmedika Indonesia - Desti Chairunisa (Universitas Budi Luhur, 2022)
Payroll is considered a structure that plays an important role in various sectors with relevant data that it contributes. Meanwhile, the payroll system simplifies the process of collecting payroll data for employees. Currently, there are many applications that are being developed to help facilitate the calculation of employee payroll. Payroll applications make it easy to store and find the data needed. PT Immortal Cosmedika Indonesia has several problems, namely, the process of collecting employee data every month is still recorded in a special book and the submission of conventional payroll reports. The purpose of this study is to help the finance department of PT Immortal Cosmedika Indonesia reduce registration and payroll errors. This research uses the Research and Development (R&D) method with a data collection method which includes observation and interviews. This application was developed using Java Netbeans 8.2 and MySQL software as its database. The result of this research is that this application can be used to help facilitate and accelerate the work of the finance department of PT Immortal Cosmedika Indonesia in terms of employee data processing, employee salary processing, employee bonus processing and providing salary slips to employees without using paper as a printed medium. And make the stored reports in good condition and provide results quickly and accurately.